Improved Learning outcomes of Volleyball Bottom Passing through M-Card Games in High School Students - Mahmudin Mahmudin; Bangkit Seandi Taroreh (Edumaspul: Jurnal Pendidikan, 2023)
The goal to be achieved in this study is to improve the enthusiasm and skills of students in learning volleyball. The method used is Classroom Action Research or often referred to as action research, where this research will be carried out through several cycles in the hope that there will be an increase in the results to be achieved. There are several experts who propose classroom action research models with different charts, but broadly speaking there are four stages that are commonly used, namely: (a) Learning Planning, (b) Action Implementation, (c) Observation and (d) Reflection. KKM (Minimum Completeness Criteria) is the lowest criterion to declare students to achieve completeness. The teacher or group of teachers determines the KKM of the subject by considering three aspects of criteria, namely complexity, carrying capacity, and intake of students. Based on the results of research in the discussion of improving the lower passing skills of the volleyball game through the M-Card method of grade X students of SMK Aisyiyah Insan Utama Prabumulih can be concluded as follows: Pre-Cycle obtained an achievement rate of 21% Cycle I obtained an achievement level of 57% including the low category, Cycle II obtained an achievement level of 92% including the high category. Through the M-Card method on learning to pass under volleyball can improve the skills of passing under the volleyball game. This is in accordance with the observations of researchers who have been made on students starting from Pre-Cycle Cycle I to Cycle II so that the M-Card method can improve Bottom Passing in volleyball games